PEREMPUAN DAN KESENJANGAN IPTEK - Harini, Sri (Pusat Studi Gender UIN Maulana Malik Ibrahim Malang, 2009)
The role of women in our country today has grown rapidly in all fields, in- cluding the development of science and technology. It is not separated from service Raden Kartini Maya memeperjuangkan have equal rights between men and women. But on the other hand it must be admitted also that in fact there are still wide gaps between groups of highly educated women to men on how to view on the role of women in science and technology devel- opment. Even more extreme again why women are always left behind his achievements in the field of science and technology than men, although there are few women in science and technology achievements are not inferior to men.Keywords: Perempuan, Kesenjangan, ilmu pengetahuan dan Teknologi.